Design and Simulation of Quadrature Phase Detection in Electrical Capacitance Volume Tomography - Imamul Muttakin; Arbai Yusuf; Rohmadi Rohmadi; Wahyu Widada; Warsito P. Taruno (Universitas Ahmad Dahlan, 2015)
Capacitance measurement accuracy is affected by phase conformity between signal and reference. This work describes phase detection scheme which is necessary for phase synchronization in tomography application. Core processing for calculating phase and amplitude of the detected signal was built on FPGA (Field-Programmable Gate-Array) platform. Phase shift demodulation algorithm employs IP core provided by Xilinx FPGA. Direct digital synthesizer (DDS), multiplier, accumulator, and CORDIC (coordinate rotation digital computer) modules were used as excitation-reference signal generator, signal multiplication, accumulation, and conversion to polar coordinate in order to conduct trigonometric operation respectively. Hardware design was emulated on MATLAB-Xilinx System Generator to observe its performance. Phase detection range 0-114.58o and mean absolute error 0.58o have been achieved. Data processing rate solely at digital signal stage was approximately 100data/s suitable for 32-channel electrical capacitance volume tomography (ECVT) system.